Emergence agitation in pediatric anesthesia: current features - da Silva, Leopoldo Muniz [UNESP]; Braz, Leandro Gobbo [UNESP]; Módolo, Norma Sueli Pinheiro [UNESP] (Sociedade Brasileira de Pediatria, 2008)
Objective: Postoperative agitation in children is a well-documented clinical phenomenon with incidence ranging from 10% to 67%. There is no definitive explanation for this agitation. Possible causes include rapid awakening in unfamiliar settings, pain (wounds, sore throat, bladder distension, etc.), stress during induction, hypoxemia, airway obstruction, noisy environment, anesthesia duration, child's personality, premedication and type of anesthesia. The purpose of this paper is to discuss the possible causes of postoperative agitation in children, providing a foundation for better methods of identifying and preventing this problem.Sources: MEDLINE and PubMed were searched using the following words: emergence, agitation, incidence, etiology, diagnosis, treatment, children, pediatric, anesthesia.Summary of the findings: This study includes a review of potential agitation trigger factors and a proposal for a standardized diagnostic score system, in addition to measures to improve prevention and treatment.Conclusion: No single factor can identified as the cause of postoperative agitation, which should therefore be considered a syndrome made up of biological, pharmacological, psychological and social components, and which anesthesiologists and pediatric intensive care specialists should be prepared to identify, prevent and intervene appropriately as necessary.